2016
DOI: 10.1186/s13287-016-0421-1
|View full text |Cite
|
Sign up to set email alerts
|

P311 induces the transdifferentiation of epidermal stem cells to myofibroblast-like cells by stimulating transforming growth factor β1 expression

Abstract: BackgroundEpithelial to mesenchymal transition, especially to myofibroblasts, plays an important role in wound healing, fibrosis, and carcinogenesis. Epidermal stem cells (EpSCs) are responsible for epidermal renewal and wound re-epithelialization. However, it remains unclear whether and how EpSCs transdifferentiate into myofibroblasts or myofibroblast-like cells (MFLCs). Here, we provide the first evidence showing that P311 induces EpSC to MFLC transdifferentiation (EpMyT) via TGFβ1/Smad signaling.MethodsWoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Microvascular endothelial cells are the principal parenchymal cells participating in wound angiogenesis (Tonnesen et al, 2000 ) that involves a phenotypic alteration of endothelial cells, directed migration, and various mitogenic stimuli (Li et al, 2003 ). Our previous studies demonstrated that P311 was a crucial factor in wound healing (Li et al, 2016 ; Yao et al, 2017 ). However, the possible role of P311 in cutaneous wounds angiogenesis was still unknown.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Microvascular endothelial cells are the principal parenchymal cells participating in wound angiogenesis (Tonnesen et al, 2000 ) that involves a phenotypic alteration of endothelial cells, directed migration, and various mitogenic stimuli (Li et al, 2003 ). Our previous studies demonstrated that P311 was a crucial factor in wound healing (Li et al, 2016 ; Yao et al, 2017 ). However, the possible role of P311 in cutaneous wounds angiogenesis was still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Following firstly identified to expressed in the embryonic brain in mice by Studler (Studler et al, 1993 ), P311 was found to express in almost all kinds of cells, like motoneurons (Fujitani et al, 2004 ), kidney tubular epithelial cells (Yao et al, 2015 ), glioblastomas (McDonough et al, 2005 ), epidermal stem cells (Li et al, 2016 ), fibroblast (Tan et al, 2010 ; Cheng et al, 2017 ), smooth muscle cells (Badri et al, 2013 ), which implied wide biological functions of P311. Actually, P311 has been shown to promote the nerve (Fujitani et al, 2004 ) and lung regeneration (Zhao et al, 2006 ), glioma invasion (McDonough et al, 2005 ), and to induce myofibroblast differentiation (Pan et al, 2002 ; Tan et al, 2010 ; Li et al, 2016 ), cell migration (McDonough et al, 2005 ; Yao et al, 2017 ). Moreover, a decreased vascular smooth muscle cell contractility, hypotonic blood vessels, and vascular hypotension was found in P311 knockout mice compared with the wild type (Badri et al, 2013 ), and even a changed behavioral responses in learning and memory (Taylor et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse EpSCs were isolated from newborn (aged 0–2 days) mouse skin, according to a method described previously [1]. Briefly, the mouse skin tissues were incubated in 0.5% dispase II in 0.9% NaCl solution overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cutaneous wounds resulting from conditions such as trauma, burns, surgery, and diabetes are common clinical problems [1]. However, how wound healing is effectively promoted, as well as how chronic refractory wounds are treated, is not well understood.…”
Section: Introductionmentioning
confidence: 99%